Alternative Method for Evaluation of DaGang Deep Drilling Applications - Sorooshian, Shahryar (Electronic Journal of Geotechnical Engineering, 2015)
Deeper oil and gas drilling is one of the main concerns caused by of the exploration and development updated technologies and problems. The high cost of deep drilling followed by the complex geological conditions in deep strata of the DaGang oilfield leads some researchers to suggest some decision making methods for evaluating the DaGang deep drilling applications. This article tries to strengthen the mention studies, with suggesting and testing an alternative decision method. Compare to previous studies with complex multi-criteria mathematical decision making methods, the suggested method of this article is more mathematical user friendly and more suitable for design makers with less mathematical knowledge. This article suggests and tests theSimple Additive Weighting (SAW) method which is a valid accurate method of decision making. KEYWORDS: Deep drilling; DaGang oilfield; Simple Additive Weighting (SAW).